2019
DOI: 10.1155/2019/1071036
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical Administration of the Complement C3 Receptor Antagonist Trifluoroacetate Modulates Microglia Reaction after Brain Injury

Abstract: Worldwide, millions of individuals suffer an ischemic stroke each year, causing major disability, especially in the elderly, where stroke is the number one cause of disability. However, to date, no effective therapy exists that targets the functional recovery after stroke. After necrosis, neuroinflammation is a common feature of the acute stroke and a major obstacle to tissue restoration. In the lesioned area, the dying neurons release chemotactic signals, such as fractalkine/CX3CL1, which evoke “eat-me” signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Some studies have shown that the dying neurons in the lesion area release chemokines such as CX3CL1, which cause “eat me” signals to be exposed, and subsequently recognized by C3aR‐expressing microglia, leading to the phagocytosis of living neurons. The C3aR antagonist SB290157 can reduce neuronal death by limiting secondary phagocytosis after stroke 97 . Correspondingly, in our study (not yet published), we observed that a large number of activated microglia aggregated and phagocyted neurons in the peri‐infarct area in the acute phase of ischemic stroke.…”
Section: Nervous System Disease Related To Pathological Microglial Phsupporting
confidence: 84%
“…Some studies have shown that the dying neurons in the lesion area release chemokines such as CX3CL1, which cause “eat me” signals to be exposed, and subsequently recognized by C3aR‐expressing microglia, leading to the phagocytosis of living neurons. The C3aR antagonist SB290157 can reduce neuronal death by limiting secondary phagocytosis after stroke 97 . Correspondingly, in our study (not yet published), we observed that a large number of activated microglia aggregated and phagocyted neurons in the peri‐infarct area in the acute phase of ischemic stroke.…”
Section: Nervous System Disease Related To Pathological Microglial Phsupporting
confidence: 84%
“…This raises the intriguing possibility that functional C3aR1 protein expression could be induced by microglia activation, and that the stimulatory effects of TLQP21 in vivo become significant under disease conditions only. Indeed, recent studies demonstrated ameliorating effects in the tau pathology of an animal model of AD by deletion of C3aR1 (Litvinchuk et al, 2018) and a reduction in inflammatory microglial density after stroke by intracortical injection of SB290157 (Surugiu et al, 2019), the same C3aR1 blocker that was used in our study.…”
Section: Discussionmentioning
confidence: 60%
“…Cleavage of C3 generates both C3a and C3b, and C3a apparently activates microglia via C3a receptors (C3aR), which acutely stimulates phagocytosis (Lian et al., 2016) and may be chemotactic for microglia (Surugiu et al., 2019). C3aR antagonists prevented microglial phagocytosis of neurons in vivo (Surugiu et al., 2019), and C3aR knock‐out prevented microglial phagocytosis of synapses (Vasek et al., 2016).…”
Section: Phagocytic Signallingmentioning
confidence: 99%